Management Strategies for Maize Cultivation in Drylands through Soil Tillage Techniques and Fertilizer Efficiency - Arum Dewi, Pervitara; Mulyati, Mulyati; Suwardji, Suwardji (Jurnal Biologi Tropis, 2024)
Dryland in Indonesia covers approximately 75.6% of the total land area, with a significant portion utilized for agriculture, including maize cultivation. However, the main challenge in maize farming on dryland is the low organic matter content and soil fertility, which can affect growth and yield. This study aims to review various soil tillage techniques and the application of both organic and inorganic fertilizers in maize cultivation on dryland. The soil tillage techniques examined include no-tillage, minimum tillage, and intensive tillage, focusing on fertilization efficiency and the sustainability of land management practices. The methodology employed was a literature review, analyzing publications indexed in SINTA and/or Scopus between 2019 and 2024. The results of the study indicate that the minimum tillage treatment provided the best results, with phosphorus availability of 17.55 mg/kg, potassium of 0.78 cmol/kg, and an increase in organic carbon to 2.44%, along with a slightly alkaline soil pH of 7.65. Minimum tillage was found to be effective in improving soil fertility without causing significant changes in pH, making it the best option for sustainable maize cultivation on dryland.